The training occupation as the basis for lifelong learning in the employment biography - Hackel, Monika [Verfasser]; Mpangara, Miriam [Verfasser] (My University, 2017)
"Vocational education and training in German-speaking countries is tradi-tionally aligned to the concept of the training occupation. Both the precise nature of this concept and the requirements made of it have regularly shifted in the past. The present article provides an overview of this development and describes current action areas with regard to structuring the training occupation in a future-oriented way so as to serve as the starting point for a flexible employment biography." (author's abstract ; BIBB-Doku)
Der Ausbildungsberuf als Grundlage lebenslangen Lernens in der Erwerbsbiografie
Keywords: S 1.3 Berufliche Erstausbildung; T 1.2 Historische Berufsbildungsforschung; L 1.1.2 Handlungs- und Lernfeldorientierung; Berufsausbildung; Ausbildungsberuf; Historische Entwicklung; Beruflichkeit; Beschäftigungsfähigkeit; Handlungskompetenz; Berufliche Sozialisation